Case report: Long-term survival in a patient with metastatic colorectal cancer treated with trifluridine/tipiracil in the third-line setting - ELBassiouny, Mohamed (Frontiers in Oncology, 2023)
Third-line treatment with trifluridine/tipiracil (FTD/TPI) is recommended for patients with metastatic colorectal cancer (mCRC) or gastric/gastroesophageal cancer (GC) who have progressed beyond ﬁrst- and second-line therapy. We describe a patient with long-term survival following treatment with FTD/TPI. The patient, a 70-year-old woman diagnosed with right-sided mCRC (T3/N1) with metastases to the aortocaval and precaval lymph nodes, received first-line panitumumab and capecitabine for 6 months, followed by second-line bevacizumab and oxaliplatin. She had disease progression following 9 months of second-line therapy and began third-line treatment with FTD/TPI (50 mg bid). Three months after treatment initiation, lymph node involvement was reduced, and following 12 months of FTD/TPI treatment, her disease had stabilized, and she reported no treatment-related adverse events. She remained on the same dose of FTD/TPI for more than 27 months after initiating treatment, with maintenance of stable disease. This patient with mCRC demonstrated a survival benefit with FTD/TPI beyond those reported in published clinical trial data and real-world studies.